RELATIONSHIP BETWEEN ANNUAL VARIABILITY OF AUSTRALIA MONSOON WITH TROPICAL CYCLONE ACTIVITY OVER INDIAN OCEAN - ARDIANSYAH (NIM : 12808008); Pembimbing : Drs. Zadrach Ledoufij Dupe, M.Si, DICKY
Tropical cyclone is one of natural phenomenon which occur in monsoon area and may result in loss of life and property. One of the main areas of the tropical cyclone formation is over Indian Ocean. In this study, the relationship between annual variability of Australian monsoon with tropical cyclone activity in the Indian Ocean has been examined. In this study, tropical cyclones data during 57 years (1949-2005) from Joint Typhoon Warning Center (JTWC) is used. In this study, tropical cyclone activity is examined at the time of the years of strong and weak monsoon based Australian Monsoon Index (AUSMI). The analysis examined in this study are frequency and site formation of tropical cyclones and tropical storms, circulation patterns, relative vorticity, potential intensity, and the Genesis Potential Index (GPI).From this analysis, it is generally found that the annual variability of the Australian monsoon and tropical iklon activity in the Indian Ocean has a positive correlation. Strong monsoon composite years have much more frequency and cyclones days (18 cyclones, 26 tropical storms, 264 days) compared with weak monsoon years composite (16 cyclones, 23 tropical storms, 247 days). In particular, there is a different relationship between them in different places. It is indicated by the value of the potential intensity in the Darwin station that has a significant correlation compared with Perth station. Relationship between the two by using the genesis potential index is less significant. It shows that GPI can not describe the relationship between annual variability of Australian monsoon with tropical cyclone activity over Indian Ocean.